2021
DOI: 10.3390/buildings11110500
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Geotechnical Characterization of Wet Flue Gas Desulfurization Gypsum and Its Potential Application as Building Materials

Abstract: In South Africa, coal represents the primary source of energy used for electricity generation. Coal power plants use the wet flue gas desulfurization (WFGD) process to remove sulfur dioxide (SO2) from their flue gas. However, this technology produces a large amount of synthetic gypsum, resulting in waste disposal and environmental pollution. This study investigated the physical, chemical and geotechnical properties of WFGD gypsum and its potential application to develop cement-free bricks. WFGD gypsum was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…As the content of CaSO 4 •2H 2 O in the industrial byproduct gypsum usually reaches 70%, its CaO and SO 3 contents are more than 70%, and the remainder contains a small amount of SiO 2 and Al 2 O 3 [1,28]. Various forms of gypsum may contain distinct impurities.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the content of CaSO 4 •2H 2 O in the industrial byproduct gypsum usually reaches 70%, its CaO and SO 3 contents are more than 70%, and the remainder contains a small amount of SiO 2 and Al 2 O 3 [1,28]. Various forms of gypsum may contain distinct impurities.…”
Section: Characteristicsmentioning
confidence: 99%
“…The industrial byproduct gypsum refers to the byproduct or waste residue generated by chemical reactions in industrial production with calcium sulfate as the main component. It is also known as chemical gypsum or industrial waste gypsum, and the main component is calcium sulfate dihydrate (CaSO 4 •2H 2 O) [1]. According to the output industry and species, the industrial byproduct gypsum mainly includes desulfurization gypsum, phosphogypsum, titanium gypsum, citrate gypsum, fluorogypsum, and salt gypsum.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the content of DG increased to 80%, the compressive strength of Specimen S-5 (20% PC, 80% DG) at any given curing age had no further growth but rather a slight decrease compared to that of Specimen S-4 (40% PC, 60% DG), indicating that once DG content exceeds 60%, C-S-H formation cannot be further promoted. Thus, the precipitation, crystallization, and growth of gypsum are severely hindered [31]. Therefore, the addition of DG cannot only reduce the PC amount and preparation cost, but also improve the compressive strength.…”
Section: Effect Of Dg Dosage On Compressive Strengthmentioning
confidence: 99%
“…The above studies have identified promising ways to utilize the resource of FGDG. However, most of them are limited to using FGDG either as retarder or mineral additive, the safe consumption of which is low, thus preventing its large-scale application [ 15 ]. FGDG is a calcium sulfate mineral with potential as a raw material for the preparation of polymer materials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%